2007
DOI: 10.1038/bdj.2007.23
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect individual tooth prognosis and choices in contemporary treatment planning

Abstract: • Attaining an accurate prognosis of periodontally involved teeth is problematic.• The reporting of success rates in endodontic literature is confused by the defi nition of 'success/failure'.• Heroic attempts to maintain teeth with poor prognosis should be questioned. Implants should not be 'the last resort' and only used when all conventional therapies have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…(25) Mandel concluded in his study that high saliva concentration was found in heavy calculus former then in slow formers . 2 Sewon L A et al reported that calcium concentration of supragingival plaque was higher in adult periodontitis patients when compared with juvenile periodontitis. (26) Also high calcium concentration of plaque is associated with low caries experience.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(25) Mandel concluded in his study that high saliva concentration was found in heavy calculus former then in slow formers . 2 Sewon L A et al reported that calcium concentration of supragingival plaque was higher in adult periodontitis patients when compared with juvenile periodontitis. (26) Also high calcium concentration of plaque is associated with low caries experience.…”
Section: Disscussionmentioning
confidence: 99%
“…It requires a 2-to 3-mm threshold change before a site can be deemed as having experienced significant breakdown. (2) Therefore, there is a requirement of developing new screening or diagnostic tools which are non-invasive, reliable, economic and can be incorporated in clinical practice, andcould be used as a risk predictor of periodontal disease. Saliva may offer the basis for a patient specific diagnostic test for periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, an accurate prognosis is crucial to the development of an appropriate treatment plan (Mordohai, Reshad, Jivraj, and Chee 2007). There are many ways multivariate survival trees can be used to help clinicians make better decisions and improve patient care.…”
Section: R> Molar_training Molar_testmentioning
confidence: 99%
“…Endodontic treatments have been shown to successfully retain compromised teeth which were fractured, carious, or traumatised [1], for many decades. However, modern developments in implant provision provide greater choice for patients and clinicians, and, therefore, the decision between a root canal therapy and implant treatment is a commonly occurring dilemma in practice.…”
Section: Introductionmentioning
confidence: 99%